School-based nutrition interventions in the Islamic Republic of Pakistan: A scoping review - Basil H. Aboul-Enein; MoezAlIslam E. Faris; Patricia J. Kelly; Teresa Keller; Nada Benajiba (Journal of Health, Population and Nutrition, 2026)
Abstract Background School-based nutrition interventions are a pivotal strategy for addressing the high burden of malnutrition in Pakistan, where stunting and wasting affect approximately 40% and 18% of children, respectively. This scoping review aims to map, characterize, and synthesize the existing evidence on school-based nutrition interventions in the Islamic Republic of Pakistan, identifying key implementation modalities, reported outcomes, and critical research gaps. Methods Guided by JBI methodology and PRISMA-ScR standards, a systematic search was conducted across 14 electronic databases (2005–2025). We included peer-reviewed studies focusing on children and adolescents (ages 5–19) in primary and secondary settings. Interventions were categorized into three modalities: food provision, micronutrient supplementation, and nutrition education. Results Thirteen studies met the eligibility criteria. Direct food-based interventions, including school feeding programs and fortified foods, demonstrated the greatest impact on child nutritional status, with reductions in wasting of up to 45% ( p < 0.001), underweight by 21.7–22% ( p < 0.001), and stunting by 6% ( p < 0.001). Additional school feeding interventions were also reported to reduce wasting and underweight significantly (both p < 0.0001), although improvements in stunting were inconsistent. Micronutrient supplementation showed inconsistent effects on anemia, with one longitudinal study reporting no significant reduction in the prevalence of anemia compared with controls. Nutrition education interventions consistently improved nutrition knowledge and literacy, with significant gains in micronutrient knowledge ( p < 0.05), nutrition knowledge retention ( p = 0.00), and fruit and vegetable knowledge, attitudes, and practices ( p < 0.05). However, corresponding improvements in dietary behaviors were inconsistent across studies. Conclusion School-based interventions show promise for addressing Pakistan’s high malnutrition burden (40% stunting, 18% wasting), but evidence is limited by methodological heterogeneity and short intervention duration. Given the absence of operational school feeding programs in Pakistan, these findings provide critical evidence for developing national policies. High-quality, longitudinal trials are urgently needed to confirm sustainability and guide scale-up.